2006
DOI: 10.1183/09031936.06.00075405
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chemo-responsiveness in patients with sleep apnoea and end-stage renal disease

Abstract: Although sleep apnoea is very common in patients with end-stage renal disease, the physiological mechanisms for this association have not yet been determined. The current authors hypothesised that altered respiratory chemo-responsiveness may play an important role.In total, 58 patients receiving treatment with chronic dialysis were recruited for overnight polysomnography. A modified Read rebreathing technique, which is used to assess basal ventilation, ventilatory sensitivity and threshold, was completed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 43 publications
6
65
0
4
Order By: Relevance
“…Second, ventilation control is known to be instable in CKD patients. Because chemoreflex responsiveness has been reported to be augmented in patients with end-stage renal disease, possibly because of the accumulation of uremic molecules or metabolic acidosis, this destabilized respiratory control-as explained by a high "loop gain" theory-can contribute to the pathogenesis of OSA (27). Although these two mechanisms have been established in hemodialysis patients, it is plausible that they are also applicable to the nondialysis CKD population.…”
Section: Discussionmentioning
confidence: 94%
“…Second, ventilation control is known to be instable in CKD patients. Because chemoreflex responsiveness has been reported to be augmented in patients with end-stage renal disease, possibly because of the accumulation of uremic molecules or metabolic acidosis, this destabilized respiratory control-as explained by a high "loop gain" theory-can contribute to the pathogenesis of OSA (27). Although these two mechanisms have been established in hemodialysis patients, it is plausible that they are also applicable to the nondialysis CKD population.…”
Section: Discussionmentioning
confidence: 94%
“…Displacement of fluids from the lower limbs increases neck circumference and pharyngeal resistance and reduces upper air way cross sectional area, contributing to the pathogenesis of obstructive sleep apnea (OSA). Pharyngeal cross sectional area in patients on CHD was smaller than the control, suggesting that this may predispose to upper airway occlusion during sleep (22). Conversion from CHD to NHD is associated with an increase in pharyngeal cross sectional area, possibly due to improve fluid removal (31).…”
Section: Pathogenesis-figurementioning
confidence: 99%
“…Sleep apnea is caused by both impaired central ventilatory control and upper air way occlusion during sleep. Enhanced ventilatory sensitivity to hypercapnea correlates with apnea severity (22). Conversion from conventional Hemodialysis (CHD) to nocturnal Hemodialysis (NHD) has been associated with reduced severity of sleep apnea due to reduction in ventilatory sensitivity to hypercapnea (31).…”
Section: Pathogenesis-figurementioning
confidence: 99%
“…Chemoreflex responsiveness has been reported to be augmented in patients with CKD V, possibly because of the accumulation of uremic molecules or metabolic acidosis, explained by a high ''loop gain'' theory, which contributes to the pathogenesis of OSA in CKD. 21 Upper airway dilator muscle dysfunction secondary to neuropathy or myopathy associated with either chronic uratemia or the underlying cause of CKD, such as diabetes mellitus can attribute to OSA. 22 There is a paucity of data in the Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…1,14,[17][18][19][20] Beecroft et al reported that the pharyngeal cross-sectional area measured by pharyngometry in ESRD patients was 12% less than that in the normal renal function control group matched for BMI. 21 Such pharyngeal narrowing was considered to occur because of upper airway edema due to systemic fluid overload and upper airway dilator muscle dysfunction due to neuropathy or myopathy associated with chronic uremia. Ventilation control is known to be unstable in CKD patients.…”
Section: Introductionmentioning
confidence: 99%